(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the specifics of using content and language integrated learning (CLIL) in teaching Russian as a foreign language. The theoretical foundations of the approach, its advantages, methodological principles and practical aspects of implementation at various stages of language training are analyzed. Particular attention is paid to the role of subject content in the formation of intercultural communicative competence and motivation of students.